2020
DOI: 10.5398/tasj.2020.43.4.322
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mineral Contents in Milk of Dairy Cattle Fed Elephant Grass Planted at Ex-Coal Mining Land

Abstract: The growth of several types of grass in the area of mine re-vegetation is rapidly providing an opportunity to be used as forages despite the possibility of heavy metal contamination. The purpose of the study was to evaluate the effect of treatment of different levels of elephant grass (EG) (Pennisetum purpureum) planted at ex-coal mining reclamation on milk productivity and mineral contents of dairy cattle. This study used four lactating (second lactation) dairy cattle using Latin Square Design of 4 (treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…If the heavy metal concentrations found in this study are compared to those found in a previous study by Salundik et al (2012), who reported Pb concentrations in 9 fresh milk samples from Bogor, West Java, at all in not detected (LOD was 400 ng/g), Harmini et al (2020) reported Hg and Pb concentrations in the fresh milk from East Kalimantan ranged at 5-7 ng/g and 5-6 ng/g respectively, and Rohmawati & Wibowo (2021) reported Pb concentrations in the fresh milk from Boyolali, Central Java, ranged at 38-57 ng/g. It can be seen that the fresh milk samples from Jakarta were relatively of better quality than those from the other provinces in Java and comparable to those from a province in Kalimantan, a separate island from Java and has a much smaller population.…”
Section: Discussionmentioning
confidence: 55%
“…If the heavy metal concentrations found in this study are compared to those found in a previous study by Salundik et al (2012), who reported Pb concentrations in 9 fresh milk samples from Bogor, West Java, at all in not detected (LOD was 400 ng/g), Harmini et al (2020) reported Hg and Pb concentrations in the fresh milk from East Kalimantan ranged at 5-7 ng/g and 5-6 ng/g respectively, and Rohmawati & Wibowo (2021) reported Pb concentrations in the fresh milk from Boyolali, Central Java, ranged at 38-57 ng/g. It can be seen that the fresh milk samples from Jakarta were relatively of better quality than those from the other provinces in Java and comparable to those from a province in Kalimantan, a separate island from Java and has a much smaller population.…”
Section: Discussionmentioning
confidence: 55%
“…Milk yield production from supplemented dairy cows with commercial blend essential oils (500 mg/kg DM) also increased (Ferreira de Jesus et al, 2016). The increased milk production with blended essential oils addition correlated with the fermentation process in the rumen (Calsamiglia et al, 2007;Harmini et al, 2020). In ruminal fermentation, blended essential oils promote the lowering ratio of acetate and propionate, resulting in reduced methane energy production (Calsamiglia et al, 2007;Juniper et al, 2006).…”
Section: Milk Productionmentioning
confidence: 98%
“…Singh et al (2016) showed that there were non-significant differences in the percentages of milk fat, protein, lactose, and SNF after the mineral mixture was added to lactating dairy cows and buffaloes for 30 days. Harmini et al (2020) examined the several diets containing various minerals; and reported no changes in protein, fat, lactose, and SNF, but there were significant differences in milk mineral content (Fe and Mg). Sahoo et al (2017) also added that mineral mixture supplementation did not affect the milk protein and SNF percentage of cows.…”
Section: Milk Component Content and Yieldmentioning
confidence: 99%
“…This calcium content normalizes muscle contractions and nerve performance in the heart organ. While phosphorus is an important element in the body that is not only beneficial for bones but provides a significant role for overall health [10], [11].…”
Section: A Introductionmentioning
confidence: 99%